Household demand for sanitation improvements in low-income informal settlements: A case of East African cities - Okurut, K; Charles, K (Elsevier, 2014)
Informal urban settlements present a range of challenges to sanitation provision, including low incomes, insecure tenure, low education levels, difficult topography and transitory populations. A household stratified probability survey complemented with focus group discussions and interviews was undertaken in low-income informal settlements in Kigali, Rwanda; Kampala, Uganda; and Kisumu, Kenya, to assess the household sanitation demand status and identify the barriers and catalysts to demand for sanitation improvements in these areas and between the cities.A five progressive decision-stage sanitation demand model revealed that similar proportions of respondents had already installed systems in Kigali (13.2%) and Kampala (12.5%), but less than 1.0% in Kisumu. However, there was a higher proportion in Kigali for each of the categories of Preference, Intent and Choice. In Kisumu, only 3.2% of respondents indicated that they had considered installing (or installed) a household sanitation facility. Reported barriers and catalysts varied between the demand stages and across the cities.The differences in attitudes at the stages of demand, and between these three cities, highlight the need to tailor programmes to meet the local demand for sanitation improvements, specific for each community. © 2014 Elsevier Ltd.